High-Definition Transcranial Direct Current Stimulation of the Dorsolateral Prefrontal Cortex Modulates the Electroencephalography Rhythmic Activity of Parietal Occipital Lobe in Patients With Chronic Disorders of Consciousness - Han, Jinying; Chen, Chen; Zheng, Shuang; Yan, Xiaoxiang; Wang, Changqing; Wang, Kai; Hu, Yajuan (Frontiers in Human Neuroscience, 2022)
Background: Disorders of consciousness (DOC) are a spectrum of pathologies affecting one’s ability to interact with the external world. At present, High-Definition Transcranial Direct Current Stimulation (HD-tDCS) is used in many patients with DOC as a non-invasive treatment, but electrophysiological research on the effect of HD-tDCS on patients with DOC is limited. Objectives: To explore how HD-tDCS affects the cerebral cortex and examine the possible electrophysiological mechanisms underlying the effects of HD-tDCS on the cerebral cortex. Method: A total of 19 DOC patients were assigned to HD-tDCS stimulation. Each of them underwent 10 anodal HD-tDCS sessions of the left dorsolateral prefrontal cortex (DLPFC) over 5 consecutive days. Coma Recovery Scale-Revision (CRS-R) scores were recorded to evaluate the consciousness level before and after HD-tDCS, while resting-state electroencephalography (EEG) recordings were obtained immediately before and after single and multiple HD-tDCS stimuli. Depending on whether the CRS-R score increased after stimulation, we classified the subjects into responsive (RE) and non-responsive (N-RE) groups and compared the differences in power spectral density (PSD) between the groups in different frequency bands and brain regions, and also examined the relationship between PSD values and CRS-R scores. Results: For the RE group, the PSD value of the parieto-occipital region increased significantly in the 6–8 Hz frequency band after multiple stimulations by HD-tDCS. After a single stimulation, an increase in PSD was observed at 10–13 Hz and 13–30 Hz. In addition, for all subjects, a positive correlation was observed between the change in PSD value in the parieto-occipital region and the change in CRS-R score in the 10–13 Hz frequency band after a single stimulation. After repeated stimulations, a positive correlation between PSD value changes and CRS-R score changes was also observed in the 6–8 Hz frequency band. Conclusion: Repeated anodal HD-tDCS of the left DLPFC can improve clinical outcomes in patients with DOC, and HD-tDCS-related increased levels of consciousness were associated with increased parieto-occipital PSD.